2022
DOI: 10.1002/smll.202204037
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Cycling All‐Solid‐State Batteries Achieved by 2D Interface between Prelithiated Aluminum Foil Anode and Sulfide Electrolyte

Abstract: All‐solid‐state batteries (ASSBs) with alloy anodes are expected to achieve high energy density and safety. However, the stability of alloy anodes is largely impeded by their large volume changes during cycling and poor interfacial stability against solid‐state electrolytes. Here, a mechanically prelithiation aluminum foil (MP‐Al‐H) is used as an anode to construct high‐performance ASSBs with sulfide electrolyte. The dense Li–Al layer of the MP‐Al‐H foil acts as a prelithiated anode and forms a 2D interface wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…According to the analysis details for Figure S12, it is concluded that, in all-solid-state batteries, the Pre In anode has the ability of improving interfacial compatibility and effective utilization of active Li, which is inseparable from the multifunctional interlayer formed on it. In comparison to other reports, ,,, sulfide-based solid-state cells in this work show superior performances in view of the cycling life span, capacity retention, and areal current density (Figure e), which proves the effectiveness of a generated interlayer on the improvement of metal anode/LPSCl interface stability.…”
supporting
confidence: 50%
“…According to the analysis details for Figure S12, it is concluded that, in all-solid-state batteries, the Pre In anode has the ability of improving interfacial compatibility and effective utilization of active Li, which is inseparable from the multifunctional interlayer formed on it. In comparison to other reports, ,,, sulfide-based solid-state cells in this work show superior performances in view of the cycling life span, capacity retention, and areal current density (Figure e), which proves the effectiveness of a generated interlayer on the improvement of metal anode/LPSCl interface stability.…”
supporting
confidence: 50%
“…Therefore, scientists are con-tinually searching for ion-conducting materials that may complement or replace existing materials to create energy storage devices for the next generation. [158,[164][165][166] Replacing liquid electrolytes with SSEs has been proposed to create all-solid-state Li-S batteries (ASSLSBs) as the optimal solution to the aforementioned difficulties; this has drawn considerable scientific interest. SSEs developed for Li-S batteries can be classified into three subcategories: inorganic, polymer, and composite.…”
Section: Solid-state Electrolytesmentioning
confidence: 99%
“…By contrast, polymer and composite SSEs exhibit better flexibility, processability, and interfacial compatibility. [162,165] Thus, polymer and composite SSEs that possess higher ionic conductivity at ambient temperatures and better mechanical strength at elevated temperatures must be urgently developed. [18] COFs are a type of organic crystalline porous material that combine the properties of polymers and inorganic crystalline materials.…”
Section: Solid-state Electrolytesmentioning
confidence: 99%
“…Compared to the polymer electrolyte and oxide electrolyte, sulfide electrolytes show more potential in commercial applications, in virtue of its high conductivity (10 −2 S cm −1 at room temperature) and malleability. [84,156,157] However, its limited electrochemical window makes inevitable compatibility and c) Reproduced with permission. [149] Copyright 2018, American Chemical Society.…”
Section: Anode Side and Solutionsmentioning
confidence: 99%